Association between dental pain and absenteeism among public workers from Southeastern Brazil - Maria Helena Monteiro de Barros Miotto; Wadson José Gonçalves Lima; Ludmilla Awad Barcellos (Revista Dor)
BACKGROUND AND OBJECTIVES:Studies carried out worldwide have shown that the incidence of dental pain is one reason leading people to look for dental services and that it impairs quality of life. This study aimed at observing the prevalence of dental pain, pain-related absenteeism and possible associations with sociodemographic characteristics.METHODS:This was an analytical, observational and transversal study using a randomized sample of 312 public servants obtained from a universe of 994 employees of the City Hall of Marataízes, ES. A structured script with 27 items was used for data collection, which was carried out between May and June 2009, by three qualified servants. Chi-square and Fisher Exact tests were used to compare dental pain percentages and absenteeism to sociodemographic factors.RESULTS:The prevalence of dental pain among employees was 57.0%, with higher prevalence among those with socioeconomic condition C/D/E (OR= 1.560). From those reporting dental pain, 17.8% have missed work, with higher prevalence of those of socioeconomic condition C/D/E (OR= 3.816) and with incomplete high school (OR= 2.298).CONCLUSION:High dental pain prevalence was observed and enough to produce absenteeism, with higher frequency among workers of less favored economic classes and with lower education level.